Invasions, DNA barcodes, and rapid biodiversity assessment using ants of Mauritius - Smith, M Alex (BioMed Central, 2009)
BACKGROUND: Using an understudied taxon (Hymenoptera, Formicidae) found on a tropical island (Mauritius) where native flora and fauna have been threatened by 400 years of habitat modification and introduced species, we tested whether estimated incidences of diversity and complementarity were similar when measured by standard morphological alpha-taxonomy or phylogenetic diversity (PD) based on a standardized mitochondrial barcode and corroborating nuclear marker. RESULTS: We found that costs related to site loss (considered loss of evolutionary history measured as loss of barcode PD) were not significantly different from predictions made either a) using standard morphology-based taxonomy, or b) measured using a nuclear marker. Integrating morphology and barcode results permitted us to identify a case of initially morphologically-cryptic variation as a new and endemic candidate species. However, barcode estimates of the relative importance of each site or network of sites were dramatically affected when the species in question was known to be indigenous or introduced. CONCLUSION: This study goes beyond a mere demonstration of the rapid gains possible for diversity assessment using a standardized DNA barcode. Contextualization of these gains with ecological and natural history information is necessary to calibrate this wealth of standardized information. Without such an integrative approach, critical opportunities to advance knowledge will be missed.